Transboundary spillovers and decentralization of environmental policies - Hilary Sigman (Rutgers University, Department of Economics, 2005)
Most US federal environmental policies allow states to assume responsibility for implementation and enforcement of regulations; states with this responsibility are referred to as “authorized” or having “primacy.” Although such decentralization may have benefits, it may also have costs with pollution spillovers across states. This paper estimates these costs empirically by studying the free riding of states authorized under the Clean Water Act. The analysis examines water quality in rivers around the US and includes fixed effects for the location where water quality is monitored to address unobserved geographic heterogeneity. The estimated equations show a 4% degradation of water quality downstream of authorized states, with an environmental cost downstream of 17 million annually.
Keywords: Q; 330; decentralization; transboundary spillovers; Grenzüberschreitende Umweltbelastung; Umweltpolitik; Gewässerbelastung; Trittbrettfahrerverhalten; Föderalismus; USA